Pectin-based edible coatings and nanoemulsion for the preservation of fruits and vegetables: a review - Hashim, Rohasmizah; Misran, Azizah (Elsevier, 2022)
Several studies have demonstrated the advantage of using of edible pectin films in preserving fruits and vegetables. Findings suggest that these films/coats act as a barrier on the surface of fruits and vegetables, which allows better moisture and water retention. It creates a good barrier by maximizing the gases accumulation and delaying ripening process. Initiatives were taken to refine food films by incorporating essential oils and other polysaccharides. These additives are a vital factor in enhancing the functional properties of pectin-based films/coatings and extending the shelf-life of fruits and vegetables. This review covers current research on different fruit and vegetable preservation processes. Fruit and vegetable safety aspects are highlighted to ensure the competencies of phenols, EOs, and nano-forms utilization in edible films/ coatings meet the purpose. Several studies have demonstrated the advantage of using of pectin edible films in preserving fruits and vegetables. Findings suggest that these films/coats act as a barrier on the surface of fruits and vegetables, which allows better moisture and water retention. It creates a good barrier by maximizing the gases accumulation and delaying ripening process. Initiatives were taken to refine food films by incorporating essential oils and other polysaccharides. These additives are a vital factor in enhancing the functional properties of pectin-based films/coatings and extending the shelf-life of fruits and vegetables. This review covers current research on different fruit and vegetable preservation processes. Fruit and vegetable safety aspects are highlighted to ensure the competencies of phenols, EOs, and nano-forms utilization in edible films/ coatings meet the purpose.